UNITY OF MIND, HEART AND BODY - Corner, Creative (Journal of Pakistan Psychiatric Society, 2022)
To the casual eye, the whirling ritual known as ‘sema’, may appear to be a theatrical performance, but it is actually a sacred Muslim religious ritual performed as part of praying by the Mevlevi Order. This order is about 750 years old, and is a living tradition based on the teachings of Rumi, also known as Mevlana, who is perhaps Turkey’s most celebrated poet and second only to Hafiz in Iran. The Mevlevis or the “whirling dervishes, as they are called” due to their famous practice of whirling as a form of remembrance of “The Al Mighty.” Mevlevis believe that during the sema ritual, the soul is freed from its earthly bonds and able to continue its journey freely. The ritual of ’whirling’ brings the Dervish into harmony with nature, while they thank and pray to “The Creator”. Sema brings together the three basic components of human nature: mind, heart, and body.